The chief rabbi's funeral : the untold story of America's largest antisemetic riot - Seligman, Scott D. (Potomac Books, an imprint of the University of Nebraska Press, 2024)
"On July 30, 1902, tens of thousands of mourners lined the streets of New York's Lower East Side to bid farewell to the city's chief rabbi, the eminent Talmudist Jacob Joseph. All went well until the procession crossed Sheriff Street, where the six-story R. Hoe and Company printing press factory towered over the intersection. Without warning, scraps of steel, iron bolts, and scalding water rained down and injured hundreds of mourners, courtesy of antisemitic factory workers. The police compounded the attack when they arrived on the scene: under orders from the inspector in charge, who made no effort to distinguish aggressors from victims, officers began beating up Jews, injuring dozens. To the Yiddish-language daily Forverts (Forward), the bloody attack on Jews was not unlike those many Russian Jews remembered bitterly from the old country. But this was America, not Russia, and the Jewish community wasn't going to stand for such treatment. Fed up with being persecuted, New York's Jews, whose numbers and political influence had been growing, set a pattern for the future by deftly pursuing justice for the victims. They forced trials and disciplinary hearings, accelerated retirements and transfers within the corrupt police department, and engineered the resignation of the police commissioner. Scott D. Seligman's The Chief Rabbi's Funeral is the first book-length account of this event and its aftermath." --